ANALISIS YURIDIS PERAN OTORITAS JASA KEUANGAN DALAM MENGAWASI PENGGUNAAN CRYPTOCURRENCY DI INDONESIA - NIM. A1012211167, SYARIF ACHMAD FIQQIH PUTRA ALKADRIE (Jurnal Fatwa Hukum, 2025)
ABSTRACT Cryptocurrency is a rapidly growing digital investment instrument characterized by high volatility and significant risks. In Indonesia, oversight of cryptocurrency was initially under the authority of the Commodity Futures Trading Regulatory Agency (Bappebti), but has since been transferred to the Financial Services Authority (OJK) in accordance with Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (P2SK Law). This study analyzes the supervisory challenges faced by Bappebti and the emerging role of OJK as the new regulatory authority. The findings indicate that Bappebti faced limitations in regulation and consumer protection, while the increasing value of transactions and the growing number of crypto investors pose potential risks to financial system stability. Based on discussions between Bappebti and the Fiscal Policy Agency (BKF), as well as reports from the Financial Stability Board (FSB), it is concluded that the rapid growth of cryptocurrency brings the potential for complexity in maintaining financial sector stability. Therefore, the decision to transfer regulatory authority to OJK represents a forward-looking government policy aimed at anticipating future challenges in the digital financial sector. The delegation of authority to OJK is considered a strategic move by the government to address the evolving dynamics of the digital financial landscape. With the issuance of OJK Regulation Number 27 of 2024, OJK now holds more comprehensive supervisory powers within the digital financial asset ecosystem. ABSTRAK Cryptocurrency merupakan instrumen investasi digital yang berkembang pesat namun memiliki volatilitas tinggi dan risiko signifikan. Di Indonesia, pengawasan terhadap cryptocurrency awalnya dilakukan oleh Bappebti, namun kini dialihkan kepada OJK sesuai dengan UU Nomor 4 Tahun 2023 tentang P2SK. Penelitian ini menganalisis kendala pengawasan oleh Bappebti serta peran OJK sebagai otoritas baru. Hasil penelitian menunjukkan bahwa Bappebti memiliki keterbatasan dalam regulasi dan perlindungan konsumen, sementara peningkatan nilai transaksi dan jumlah investor kripto berisiko terhadap stabilitas sistem keuangan. Berdasarkan hasil diskusi antara Bappebti, Badan Kebijakan Fiskal (BKF), serta laporan dari Financial Stability Board (FSB), disimpulkan bahwa pertumbuhan pesat cryptocurrency membawa potensi kompleksitas terhadap stabilisasi sektor keuangan. Oleh karena itu, keputusan untuk mengalihkan pengawasan ke OJK merupakan bentuk kebijakan forward looking pemerintah dalam mengantisipasi tantangan sektor keuangan digital masa depan.. Pengalihan kewenangan ke OJK dianggap sebagai langkah strategis pemerintah menghadapi tantangan sektor keuangan digital. Dengan terbitnya POJK Nomor 27 Tahun 2024, OJK kini memiliki wewenang pengawasan yang lebih komprehensif dalam ekosistem aset keuangan digital. Kata Kunci: Otoritas Jasa Keuangan, Cryptocurrency, Bappebti, Pengawasan, Peralihan